TAHAP PERANCANGAN LOGO INSPIRASI (INDONESIA–NTU SINGAPORE INSTITUTE OF RESEARCH FOR SUSTAINABILITY AND INNOVATION) - Pratama putra, Yudha (Wimba : Jurnal Komunikasi Visual, 2024)
The Ministry of Education and Culture (Kemdikbud) in collaboration with UGM, UI, ITB, ITS, and NTU Singapore has initiated the INSPIRASI Program (Indonesia–NTU Singapore Institute of Research for Sustainability and Innovation). These five universities, with funding from LPDP, aim to establish centers of excellence to attract researchers, students, and industry partners to create concrete solutions for climate change mitigation and sustainability. INSPIRASI focuses on three main pillars: Renewable Energy, Circular Economy, and Smart Cities, involving aspects of research, education, enterprise, and community. This design-based research aims to produce the INSPIRASI logo and brand guidelines. The method used is descriptive qualitative, and the logo design method follows Robin Landa's 5-stage model: Orientation, Analysis, Concept Design, Design, and Implementation. The logo design is inspired by the international Atom Symbol, depicting three well-defined electron orbits around a nucleus. The three electron orbits represent the three main pillars, while the atom's nucleus represents the aspects of research, education, enterprise, and community.